Pedagogical ethics, the educator’s communication etiquette, and pedagogical technique: the role of self-education and self-improvement in pedagogical mastery. - G’aniyeva , Shahnoza (Journal of Pedagogical and Philological Research, 2026)
This article explores pedagogical ethics, teacher communication culture, and pedagogical techniques, emphasizing their role in self-development and professional growth. It analyzes the structural components of pedagogical mastery, individual development strategies, and perspectives of Eastern and modern scholars on the formation of a teacher’s personality.